Assistance in Increasing ICT Capabilities for Learning for Teachers at SMKN 7 Mataram - Ramdani, Fitri; Indriaturrahmi, Indriaturrahmi; Ningsih, Septia (Abdi Masyarakat, 2024)
This service activity aims to equip SMKN 7 Mataram teachers with the development of Information and Communication Technology knowledge and skills in utilizing one of the information technology applications to make teaching materials more interesting. Of the many information technologies in the world of education, Canva is an online graphic design application that allows users to create various types of visual content such as posters, brochures, presentations, and others. Canva offers various free features to various design templates to support users in creating graphic content such as creating teaching materials. Based on observations, several teachers at SMKN 7 Mataram have utilized this application as their teaching material and there are teachers who still use traditional methods of teaching because they are not used to using the Canva application. With the rapid development of technology, the Canva application also increasingly offers many features and templates to support learning media for teachers. Based on this, to help teachers at SMKN 7 Mataram, the service team provided assistance on exploring more widely the use of Canva such as how to create their own learning media templates to create learning videos. Based on the results of the evaluation carried out on the material of the mentoring activities carried out, very good results were obtained and the partners also said that they were greatly helped by the material that had been delivered by the community servant team.